PENGARUH PENGEMBANGAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI (Studi Pada Kantor Kecamatan Siluq Ngurai Kabupaten Kutai Barat) - Rusdi, Rusdi (PREDIKSI, 2016)
This study aims to determine whether the pattern of human resources competency development and performance of employees and the impact of competence development of human resources to employee performance Siluq Ngurai District of Kutai Barat. The results showed that the variable competence of human resources do not have a positive relationship with employee performance variables. It can be seen from the comparison between the value of r empirical (count) with the value of r theoretical (table) in the table prices are critical to r product moment, ie r (hit) = 0.052 < r (tab) = 0.288 at a significance level 0 05 to n = 45. This means that there is no positive relationship and influence between variable competence development of human resources with performance variables. The results show that the resulting R-Square is 0,003, which means contributions competence development of human resources to employee performance is only 0.03%. This means that there is no significant influence of the competence of human resources development variables to variable employee performance.